ANALISIS PENDAPATAN DAN DISTRIBUSI PENDAPATAN USAHATANI KARET DI KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Vina Panca Margaretha Siringoringo; Ermi Tety; Jum’atri Yusri (Fakultas Pertanian, Universitas Riau, 2020)
This research aimed to know the income and distribution of rubber farming income in Singingi District Kuantan Singingi Regency. The method used in this research is survey method. Sampling in this research taken by purposive sampling counted 60 farmers. Data analysis used in this research is income analysis and income distribution analysis. The results showed that the total income from rubber farming amounting to Rp 75,108,947 per month with an average of Rp 1,251,816 per month. Rubber farming income distribution as seen from the value of the Gini ratio index and the Lorenz curve. Gini ratio index of rubber farming 0,131 (< 0,40) to mean the income distribution on rubber farming is at a low level of inequality. The total income of the 40% lowest received Rp 20,146,439 per month, 40% intermediate received Rp 29,985,627 per month and in the highest 20% received Rp 24,976,881. Lorenz curves is a visual of the Gini ratio. The Lorenz curve of rubber farm income approaching the diagonal line or the Equalization lines perfect which means that the income of rubber farming is evenly distributed. Rubber farmers income from farming the rubber on the 40% lowest received 26.82% of total income, 40% intermediate received 39.92% of the total income and the highest 20% received 33.25% of total revenue.